2022
DOI: 10.3390/nano12040674
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots/Iron Oxide Nanoparticles with Tuneable Composition and Properties

Abstract: We present a simple strategy to generate a family of carbon dots/iron oxide nanoparticles (C/Fe-NPs) that relies on the thermal decomposition of iron (III) acetylacetonate in the presence of a highly fluorescent carbon-rich precursor (derived via thermal treatment of ethanolamine and citric acid at 180 °C), while polyethylene glycol serves as the passivation agent. By varying the molar ratio of the reactants, a series of C/Fe-NPs have been synthesized with tuneable elemental composition in terms of C, H, O, N … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…While somewhat reduced due to a significant change in the relative contribution of carbon to Figure 3 provides the FTIR spectra for the CDot and CDot-magnetite samples. The CDot sample has similar features to many reported CDot samples serving as a means of fingerprint identification of carbon dot formation [18,20,23]. An analysis of the IR spectrum shows strong OH features (>3000 cm −1 ), CH stretch (~2920), and carbonyl (~1700 cm −1 ) signatures, and a multitude of stretches within the fingerprint region.…”
Section: Wavelength (Nm)supporting
confidence: 63%
See 1 more Smart Citation
“…While somewhat reduced due to a significant change in the relative contribution of carbon to Figure 3 provides the FTIR spectra for the CDot and CDot-magnetite samples. The CDot sample has similar features to many reported CDot samples serving as a means of fingerprint identification of carbon dot formation [18,20,23]. An analysis of the IR spectrum shows strong OH features (>3000 cm −1 ), CH stretch (~2920), and carbonyl (~1700 cm −1 ) signatures, and a multitude of stretches within the fingerprint region.…”
Section: Wavelength (Nm)supporting
confidence: 63%
“…Hu et al prepared carbon-iron oxide hybrid dots via a microwave-induced solid thermal reaction and demonstrated that the photophysical properties of the CDots were not impacted by the presence of, or their interaction with, the iron oxide [17]. Stachowska et al prepared a series of C/Fe-NPs by reacting iron acetylacetonate with a pre-formed carbon nanoparticle precursor with polyethylene glycol as capping agent to produce C/Fe-NPs of varying compositions [18]. The particles were studied to determine the effect of composition on their optical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2022). Some CBM, such as CDs and their composites, can generate ROS and heat under photon irradiation to induce the death of bacteria (Chu, Wang, et al, 2022;Stachowska et al, 2022;Q. Xu, Cai, et al, 2022).…”
Section: Bacteria Elimination Based On Synergy Pdt/ptt Using Cdsmentioning
confidence: 99%
“…Wang et al, 2022). Some CBM, such as CDs and their composites, can generate ROS and heat under photon irradiation to induce the death of bacteria (Chu, Wang, et al, 2022; Stachowska et al, 2022; Q. Xu, Cai, et al, 2022). For example, one study obtained a CDs‐based composite from citric acid, urea, and cupric chloride dihydrate by a solvothermal method, in which dimethylsulfoxide was selected as the solvent.…”
Section: Cds For Bacteria Eliminationmentioning
confidence: 99%